Preparation and characterization of CU-, FE-, AG-, ZN- and NI- doped gelatin nanofibers for possible applications in antibacterial nanomedicine - Nuge, Tamrin; Tshai, Kim Yeow; Lim, Siew Shee; Nordin, Norshariza; Hoque, Md. Enamul (School of Engineering, Taylor's University College, 2017)
A facile and efficient approach to prepare metal nanoparticles doped electrospun gelatin from metal salts precursors was successfully developed. The incorporation of metal ions with antimicrobial activity into electrospun gelatin (Ge-espun) is an attractive approach to control the inflammatory reaction and prevent infection in wound. In this study, metal salts precursors AgNO3, Fe(NO3)3.9H2O, Cu(NO3)2.3H2O, Zn(NO3)2.6H2O and Ni(NO3)2.6H2O were reduced to metal nanoparticles with acetic acid as solvent and reducing agent. The agglomeration of nanoparticles was inhibited by the gelatin polymer matrix. Electrospinning of both neat Ge-espun and metal-nanoparticles/Ge-espun resulted in the formation of smooth fibres with average diameters of ~280nm and ~40nm-150nm, respectively. The efficacy of metal nanoparticles/Ge-espun against bacteria commonly found on wounds was tested with different metal loading by measuring the inhibition of colony forming units. The results indicated a broad spectrum of antibacterial activity showed by Ag/Ge-espun, followed by Fe/Ge-espun and Zn/Ge-espun. An interesting finding on the efficacy of Cu/Ge-espun and Fe/Ge-espun against the Gram’s positive bacteria is worth exploring to further investigate the potential application of metal-based antibiotics against the antibiotic-resistant bacterial strains.